The Influence of Cognitive, Affective, and Psychomotor Assessment Based on SPSS and SmartPLS Software on the Effectiveness of Learning Outcomes Evaluation Management at Senior High Schools in Jember Regency - Amin Silalahi; Basuki Hadiprayogo; Karnadi; Balthasar Watunglawar; Nugroho Edi Santoso (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study investigates the effects of cognitive, affective, and psychomotor domains on the effectiveness of learning outcome assessment management at senior high schools in Jember Regency, Indonesia. Utilizing a quantitative survey approach, data were collected from 100 teachers through validated questionnaires. Analysis employed SPSS and SmartPLS software, revealing a model with an R² of 0.999, indicating excellent explanatory power. Results demonstrated that affective (beta = 0.573) and psychomotor (beta = 0.424) domains significantly positively influence assessment management effectiveness, while cognitive (β = 0.003) shows no significant effect. These findings highlight the prominent roles of emotional and practical skills in assessment management. The integration of SPSS and SmartPLS enhances analytical precision, supporting data-driven decision-making. This research contributes to the development of technology-based assessment models, emphasizing the importance of managing affective and psychomotor domains to improve educational quality.